Fission processes in the zoanthid Palythoa caribaeorum Duchassaing & Michelotti, 1860 (Zoantharia: Sphenopidae) in the Southwest Atlantic, Brazil. - Teixeira, Larissa Marques Pires; Creed, Joel Christopher (Revista de Fotografia Científica Ambiental, 2018)
The zoanthid Palythoa caribaeorum has a wide distribution throughout benthic communities of shallow waters in the coast of Brazil. Sexual and asexual reproductive strategies are among the factors that contribute to the successful distribution of this species. We documented through underwater photography an asexual reproduction process known as fission, in P. caribaeorum, in Baía da Ilha Grande, Brazil. We believe that part of the original colony was detached from the rock and the basal coenenchyma stretched and attached to a new rock. The fission process was rarely reported by photography.